OpenStreetMap in Israel and Palestine – 'Game changer' or reproducer of contested cartographies?. (March 2017) - Bittner, Christian
Abstract: In Israel and Palestine, map-making practices were always entangled with contradictive spatial identities and imbalanced power resources. Although an Israeli narrative has largely dominated the 'cartographic battlefield', the latest chapter of this story has not been written yet: collaborative forms of web 2.0 cartographies have restructured power relations in mapping practices and challenged traditional monopolies on map and spatial data production. Thus, we can expect web 2.0 cartographies to be a 'game changer' for cartography in Palestine and Israel. In this paper, I review this assumption with the popular example of OpenStreetMap (OSM). Following a mixed methods approach, I comparatively analyze the genesis of OSM in Israel and Palestine. Although nationalist motives do not play a significant role on either side, it turns out that the project is dominated by Israeli and international mappers, whereas Palestinians have hardly contributed to OSM. As a result, social fragmentations and imbalances between Israel and Palestine are largely reproduced through OSM data. Discussing the low involvement of Palestinians, I argue that OSM's ground truth paradigm might be a watershed for participation. Presumably, the project's data are less meaningful in some local contexts than in others. Moreover, the seemingly apolitical approach to map only 'facts on the ground' reaffirms present spatio-social order and thus the power relations behind it. Within a Palestinian narrative, however, many aspects of the factual material space might appear not as neutral physical objects but as results of suppression, in which case, any 'accurate' spatial representation, such as OSM, becomes objectionable.